Consumer's satisfaction on the use of wooden furniture in Baling, Kedah - Rosli, Ainun Syahira (2019)
A study was undertaken to identify the level of consumer satisfaction and to determine the factors that influence the consumers to purchase wooden furniture in Kedah. The questionnaire was randomly distributed to the respondents around the district of baling using a simple sampling method. As a result of this study, 156 out of 209 respondents like to use the wooden furniture. Most of the respondents are satisfied with the dining set and living room set with the factors of reasonable price, durable and good quality. Although there had are unsatisfied respondents with the furniture after they purchased furniture, they still choose to buy other furniture in the same place and shop. Price is an important criterion for respondents with low monthly income and only 34 respondents with high income.